Democratic Leadership of Murabbiah nn Guiding Female Santri: A Qualitative Analysis of Behavioral and Spiritual Development - Huda, Nahdliyatul Ilmiyah; Dinda aulia Nisya; Farkhatul Fitriyah Salsabila Raharjo; M. Imamul Muttaqin (Universitas Islam Negeri (UIN) Mataram, 2025)
This study explored the role of democratic leadership, specifically as practiced by murabbiah within ma’had environments, in guiding female santri who were at risk of falling into negative social circles. The research examined the challenges faced by santri, including nicotine addiction and negative peer influence, which could threaten their values, faith, and sense of purpose. Using a qualitative descriptive approach, this study revealed that democratic leadership employed by murabbiah fostered open, supportive, and empathic communication. Through persuasive yet compassionate interactions, murabbiah were able to motivate santri to rediscover their potential and align their lives with positive religious and moral values. The findings indicated that such leadership not only addressed immediate behavioral issues but also contributed to the holistic development of the santri by strengthening their character, spirituality, and resilience.